2016
DOI: 10.4049/jimmunol.1600663
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Memory CD4+ T Cells Target Conserved Epitopes of Rhinovirus Capsid Proteins and Respond Rapidly to Experimental Infection in Humans

Abstract: Rhinovirus (RV) is a major cause of common cold and an important trigger of acute episodes of chronic lung diseases. Antigenic variation across the numerous RV strains results in frequent infections and a lack of durable cross-protection. Since the nature of human CD4+ T cells that target RV is largely unknown, T-cell epitopes of RV capsid proteins were analyzed, and cognate T cells characterized in healthy subjects and those infected by intranasal challenge. Peptide epitopes of the RV-A16 capsid proteins VP1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 82 publications
3
45
0
Order By: Relevance
“…As such, the T cell response must occur through activation of preexisting effector/memory T cells responding to common epitope(s) displayed by the infecting RV. Consistent with this, epitope mapping of RV targeting T cells had identified an HLA-DR4-restricted CD4-specific epitope of RV39 VP1 maps to a region that is conserved across RV groups A, B, and C [68••]. …”
Section: Adaptive Immune Response To Rhinovirusmentioning
confidence: 76%
“…As such, the T cell response must occur through activation of preexisting effector/memory T cells responding to common epitope(s) displayed by the infecting RV. Consistent with this, epitope mapping of RV targeting T cells had identified an HLA-DR4-restricted CD4-specific epitope of RV39 VP1 maps to a region that is conserved across RV groups A, B, and C [68••]. …”
Section: Adaptive Immune Response To Rhinovirusmentioning
confidence: 76%
“…Thus, studying this phenomenon could yield insight into the pathogenicity of T H 1 cells in asthmatic patients. After experimental infection of healthy subjects with HRV-A16, circulating HRV-specific CD4 + T cells identified by means of tetramer staining that expanded after infection were predominantly IFN-γ + 142 . Moreover, IFN-γ + CD4 + T cells are readily detected in BAL fluid from allergic asthmatic patients experimentally infected with HRV.…”
Section: Heterogeneity Of T Cells and Influence Of The Tissue Microenmentioning
confidence: 99%
“…Since there are over 160 distinct RV strains characterized to date [9], reinfection with other strains is common. Viral capsid proteins (VP) of RV contain sequences [79] and T cell epitopes [80], which are conserved across strains. erefore, humoral or cellular cross-reactivity might provide cross-strain protection against heterologous RV infection.…”
Section: Rhinovirus (Rv)mentioning
confidence: 99%
“…Co culture of DCs, RV-A39 and T cells resulted in proliferation of CD4 + and CD8 + T cells and enhanced IFNγ production. Muehling et al [80] showed that pre-existing CD4 + Tm cells, speci c to conserved epitopes of the VP region, proliferate upon RV-A16 challenge in seronegative donors. CD4 + T m cells mainly showed a 1 or T follicular helper phenotype.…”
Section: Rhinovirus (Rv)mentioning
confidence: 99%
See 1 more Smart Citation